PENGARUH INVESTMENT DECISION, FINANCING DECISION, DAN MAKRO EKONOMI TERHADAP GOOD FINANCIAL GOVERNANCE SERTA VALUE OF THE FIRM DENGAN UNSYSTEMATIC RISK DAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Sikip Nur Ika May Nur Himama; Tri Ratnawati; Nekky Rahmiyati (Universitas 17 Agustus 1945 Surabaya, 2018)
The purpose of this research is to analyze the influence of investment decision, financing decision, andmacro economy toward good financial governance and value of the firm with unsystematic risk andprofitability as intervening variable. This research is conducted at Indonesia Stock Exchange (BEI) to allmanufacturing companies listed on Indonesia Stock Exchange from 2013 to 2016. The sample used is 27manufacturing companies in Indonesia stock exchange in 2013-2016. The results showed that Based on theresults of data testing that has been carried out, a conclusion can be drawn on the results of hypothesistesting: Investment Decision has no significant effect on Unsystematic Risk and on Financing Decision buthas a significant effect on Profitability, on Good Financial Governance, Value of the Firm and on GoodFinancial Governance through Unsystematic Risk. Financing Decision has Significant Effect onUnsystematic Risk, Profitability, Good Financial Governance but has no significant effect on Value of theFirm Macroeconomics has a significant influence on Unsystematic Risk, Profitability, Investment Decisin,Decision Financing, Good Financial Governance and Value of the Firm Unsystematic Risk SignificantlyAffects Profitability and Good Financial Governance Profitability Significantly Affects Good FinancialGovernance, and Value of The Firm, and Good Financial Governance Significantly Affects Value of TheFirm Financing Decision has a significant effect on Good Financial Governance through UnsystematicRisk.Macroeconomics has a significant effect on Good Financial Governance through Unsystematic Risk.Investment Decision affects the Value of the Firm through Profitability.Decision Financing on Value of theFirm through Profitability.and Macroeconomics affects the Value of the Firm through Profitability.Keywords: investment decision, financing decision, macro economy, good financial governance,value of the firm, unsystematic risk, and profitability.